(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper deals with a fragment of a new inscription on bronze discovered in Novallas (province of Zaragoza). It is written in the Latin alphabet and in a palaeohispanic language, presumably Celtiberian. Despite its fragmentary nature, it attests a palaeo-epigraphic feature unparalleled in the western Latin epigraphy: a new kind of s. It contains also a Latin loanword: publicus.